ANALISIS KESALAHAN-KESALAHAN DALAM PENULISAN SURAT RESMI MASUK PADA ASMI DESANTA YOGYAKARTA - Kristiyanti, Iin; FX. Indrojiono (PARADIGMA: Jurnal Ilmu Administrasi, 2025)
The data in this study were analyzed descriptively and qualitatively. The data were described in the form of words or sentences, outlining errors in letter format, date, attachments, address, and pronouns in closing paragraphs of official letters received by ASMI Desanta Yogyakarta. The research subjects were official documents received by ASMI Desanta Yogyakarta. The data obtained in this study were written data in the form of official letters received by ASMI Desanta Yogyakarta. Data collection was conducted using document analysis techniques. Document analysis is a data collection technique that involves collecting, reviewing, examining, and analyzing documents in the form of official letters received by ASMI Desanta Yogyakarta, and then drawing conclusions. The results of the study showed that many letters were still typed in a manner inconsistent with the existing formal letter format. Some letters still included the city name in their date, a dash (-) was used for attachments without attachments, and the number of attachments was still written or typed with both numbers and letters. Many still used the word "to," "to," and "sir," in addressing, before the name of a person with a title, rank, or position. The second-person pronoun (-nya) was used in the closing paragraph because in writing we are communicating with a second party. The pronoun "-nya" is used for third-person pronouns. Thus, recoqnizing various mistakes will educate the letter writers in drafting future official letters to be more accurate, and as a consequence, it will futher enhance the quality of Indonesian correspondence in Indonesia.